Technology, Communication and the Performance of Financial Markets: 1840-1975 - Garbade, Kenneth D.; Silber, William L. (Journal of Finance, 1978)
Kenneth D. Garbade, William L. Silber, Technology, Communication and the Performance of Financial Markets: 1840-1975, The Journal of Finance, Vol. 33, No. 3, Papers and Proceedings of the Thirty-Sixth Annual Meeting American Finance Association, New York City December 28-30, 1977 (Jun., 1978), pp. 819-832